PERBANDINGAN HASIL BELAJAR FISIKA YANG MENGGUNAKAN MODEL PEMBELAJARAN MAKE A MATCH DENGAN MODEL PEMBELAJARAN COOPERATIVE SCRIPT DI SMA - Octaviano Octaviano; Vina Serevina; Anggara Budi Susila (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
The research aims to determine the comprison result of learning physics by using model Make A Match with Cooperative Script in high school.This research was conducted at SMAN 53 Jakarta in February-April 2015. The sample used in a class X MIA 2 as an experimental class 1, and X MIA 1 as an experimental class 2 respectively of 36 students who have the same condition.The research method is quasi experiment, the research instrument in the form of multiple choice questions with a number of about 30 items. Using the price obtained Normality Test Chi Square cunt Chi Square table, for class 1 is 7,86642 11,070 and experimen class 2 that 6,9326 11,070, based on data from second class of normal distribution. Homogeneity test resuls obtained for is 1,275 2,52 so the data is homogeneous. Based on hypothesis testing using t-test showed (2,015) and the value of (1,66691) at significance level by dk=(36-36)-2=70. Because then Ho is rejected and Ha accepted. It can be concluded that students who use learning models make a match higher than students who use Cooperative Script learning model. Keywords: Make A Match, Cooperative Script, Learning Outcomes.